PEMBERDAYAAN KARYAWAN DAN KUALITAS PELAYANAN PADA PERUSAHAAN PELAYARAN - Kadarisman, Muh; Sudewo, Gatot Cahyo; Pahala, Yosi (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
This research aims to find out the relationship of strategic management, organizational culture and employees’ empowerment with service quality. This research is carried on at PT Sillo Bahari Nusantara using quantitative approach with survey method. The population of this study is the employees at PT Sillo Bahari Nusantara Jakarta 2015. The samples used in this study are 50 respondents which are selected randomly. The data is analyzed using descriptive statistic technic and parametric inferential. Based on data analysis it can be concluded that all the independent variables like strategic management, organizational culture, and employees’ empowerment have a positive and strong relation towards service quality, either partially or simultaneously. Therefore, the service quality can be increased by improving strategic management, organizational culture and employees’ empowerment.